New training goal based technical training model in long-term beginner futsal training system - Pleshakov, A. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test by experiment a new futsal technical training system with its goals in the long-term training process. Methods and structure of the study. The new futsal technical training system testing experiment was run at Sergiev Posad Sports School in the Moscow Oblast in 2018 to 2021. We sampled for the three-year experiment the 7-9-year-old (n=36) futsal players. The futsal technical training system was customized in the training times, content and priorities as dictated by the long-term training mission and goals. The technical training was designed on a time- and cost-efficient basis by the training material being well systematized and staged to facilitate prudent sequencing of the individual technical progress. Every technical skill was mastered and excelled by special exercises so that to work out every technical element on a versatile basis, with reasonable repetitions of every motor action. Results and conclusion. On the whole, the progress was the highest in the non-lead leg and both-legs ball control skills tests. An intergroup progress analysis found the poor progress in the both-legs test in the Control Group being probably due to the backlogs and inefficiencies in the non-lead leg ball control skills training service. The new combined futsal technical training model complementary to the long-term training process was tested beneficial as it facilitates progress in the `movement schooling` process with a special focus on the relevant technical fitness and competitive progress elements. The new futsal technical training model analyzed herein is designed on a reasonably customizable basis and, hence, may be recommended for application in the beginner futsal trainings and other team sports basics training systems.